Effects of treatment of non-alcoholic fatty liver disease on heart failure with preserved ejection fraction - Yang, Zifeng; Tian, Ruifeng; Zhang, Xiao-Jing; Cai, Jingjing; She, Zhi-Gang; Li, Hongliang (Frontiers in Cardiovascular Medicine, 2023)
In the past few decades, non-alcoholic fatty liver disease (NAFLD) and heart failure with preserved ejection fraction (HFpEF) have become the most common chronic liver disease and the main form of heart failure (HF), respectively. NAFLD is closely associated with HFpEF by sharing common risk factors and/or by boosting systemic inflammation, releasing other secretory factors, and having an expansion of epicardial adipose tissue (EAT). Therefore, the treatments of NAFLD may also affect the development and prognosis of HFpEF. However, no specific drugs for NAFLD have been approved by the Food and Drug Administration (FDA) and some non-specific treatments for NAFLD are applied in the clinic. Currently, the treatments of NAFLD can be divided into non-pharmacological and pharmacological treatments. Non-pharmacological treatments mainly include dietary intervention, weight loss by exercise, caloric restriction, and bariatric surgery. Pharmacological treatments mainly include administering statins, thiazolidinediones, glucagon-like peptide-1 receptor agonists, sodium-glucose cotransporter 2 inhibitors, and metformin. This review will mainly focus on analyzing how these treatments may affect the development and prognosis of HFpEF.